Energy analysis on gas turbine power plant [microfilm] - Tan, Chee Siang (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 2003